2015
DOI: 10.3233/bmr-150604
|View full text |Cite
|
Sign up to set email alerts
|

The effects of clinical pilates exercises on bone mineral density, physical performance and quality of life of women with postmenopausal osteoporosis

Abstract: Pilates Exercises is effective to increase BMD; QOL and walking distance and also beneficial to relieve pain. Physiotherapist can use Pilates Exercises for the subjects with osteoporosis in the clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 21 publications
0
77
0
3
Order By: Relevance
“…Among the 23 included studies, six studies were conducted in Iran (Abedi, Nikkhah, & Najar, ; Asghari, Mirghafourvand, Mohammad‐Alizadeh‐Charandabi, Malakouti, & Nedjat, ; Bakhtiari et al, ; Darsareh, Taavoni, Joolaee, & Haghani, ; Kazemzadeh, Nikjou, Rostamnegad, & Norouzi, ; Taavoni, Darsareh, Joolaee, & Haghani, ), five studies were conducted in India (Chattha, Nagarathna, Padmalatha, & Nagendra, ; Jayabharathi & Judie, ; Joshi, Khandwe, Bapat, & Deshmukh, ; Sujithra, ; Vora & Dangi, ), three in Turkey (Angin, Erden, & Can, ; Basat, Esmaeilzadeh, & Eskiyurt, ; Teoman et al, ), three in China (Gao, Zhang, Qi, & Petridis, ; Hu et al, ; Zhang et al, ), three in Japan (Iioka & Komatsu, ; Kai, Nagamatsu, Kitabatake, & Sensui, ; Ueda, ), one in South Korea (Hur, Yang, & Lee, ), one in Thailand (Ngowsiri, Tanmahasamut, & Sukonthasab, ), and one in Taiwan (Yeh & Chang, ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 23 included studies, six studies were conducted in Iran (Abedi, Nikkhah, & Najar, ; Asghari, Mirghafourvand, Mohammad‐Alizadeh‐Charandabi, Malakouti, & Nedjat, ; Bakhtiari et al, ; Darsareh, Taavoni, Joolaee, & Haghani, ; Kazemzadeh, Nikjou, Rostamnegad, & Norouzi, ; Taavoni, Darsareh, Joolaee, & Haghani, ), five studies were conducted in India (Chattha, Nagarathna, Padmalatha, & Nagendra, ; Jayabharathi & Judie, ; Joshi, Khandwe, Bapat, & Deshmukh, ; Sujithra, ; Vora & Dangi, ), three in Turkey (Angin, Erden, & Can, ; Basat, Esmaeilzadeh, & Eskiyurt, ; Teoman et al, ), three in China (Gao, Zhang, Qi, & Petridis, ; Hu et al, ; Zhang et al, ), three in Japan (Iioka & Komatsu, ; Kai, Nagamatsu, Kitabatake, & Sensui, ; Ueda, ), one in South Korea (Hur, Yang, & Lee, ), one in Thailand (Ngowsiri, Tanmahasamut, & Sukonthasab, ), and one in Taiwan (Yeh & Chang, ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, while some studies also used two sessions a week (22,33,34), other studies used one session a week (24) or three sessions a week (20,29,30). There are a few inconsistencies with other studies related to the total intervention time.…”
Section: Discussionmentioning
confidence: 99%
“…The study by kalron showed that no significant differences were observed in QOL of women who did Pilates exercise and walking (19). Although there are a few studies on the relationship between the Pilates method and quality of life (12,(20)(21)(22), other studies have focused on other aspects that could contribute to improving QOL in climacteric women (23).…”
Section: Introductionmentioning
confidence: 99%
“…This study also did not have a control group. Other studies have evaluated the quality of life in individuals, who practice Pilates, with diseases such as low back pain, fibromyalgia, osteoporosis, menopause, ankylosing spondylitis and breast cancer (14)(15)(16)(17)(18)(19) . We did not find in the literature a research in methodological equivalence in terms of gender of the sample and methodological design of the study.…”
Section: Discussionmentioning
confidence: 99%